1981
DOI: 10.1021/jf00108a028
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloids of wild, tuber-bearing Solanum species

Abstract: The total glycoalkaloid (TGA) levels and individual glycoalkaloid compositions of current potato cultivare do not represent a toxicological or teratogenic hazard. However, the widespread exploitation of wild, tuber-bearing Solanum species in potato breeding programs suggests the need for caution in the future. Some species contain much higher TGA levels than are found in Solanum tuberosum (Schreiber, 1963; Osman et al., 1978). There is also widespread occurrence among these wild species of glycoalkaloids which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 12 publications
1
53
1
Order By: Relevance
“…Very little is known of GAs of S. bulbocastanum. As far as we know, only Gregory et al [13] reported the presence of unidentified GAs in the leaves of this species. The determination of the GA composition of S. tuberosum -S. bulbocastanum hybrids would be important in that it may affect either human consumption or resistance to pathogen and pests.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Very little is known of GAs of S. bulbocastanum. As far as we know, only Gregory et al [13] reported the presence of unidentified GAs in the leaves of this species. The determination of the GA composition of S. tuberosum -S. bulbocastanum hybrids would be important in that it may affect either human consumption or resistance to pathogen and pests.…”
mentioning
confidence: 85%
“…1 H-and 13 C-NMR spectra: at 600 and at 75 MHz, resp., in CD 3 OD on Bruker spectrometers; d in ppm rel. to Me 4 Si, J in Hz; 13 C multiplicities determined by DEPT spectra [22] using Bruker microprograms. ESI-MS: Micromass Q-ToF Micro instrument.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Wounding and light exposure are known to affect glycoalkaloid content, which could lead to levels beyond the threshold of 20 mg per 100 g fresh weight (Petersson et al 2013), the level considered safe for human consumption (Smith et al 1996). Many wild species of potato naturally produce high levels of glycoalkaloids (Gregory et al 1981), leading to a need to monitor glycoalkaloid content when introducing other traits from these species. Therefore breeders must be mindful of glycoalkaloid levels when using wild species to develop germplasm.…”
Section: Nutritionmentioning
confidence: 99%
“…Cultivated potatoes generally have less solanine, and cases of poisoning are rare. Tubers of wild potato species vary in the identity and quantity of glycoalkaloids present (Schrieber, 1968;Osman et al, 1978;Gregory et al, 1981;Johns and Osman, 1986). Wild species in general have 100 mg/100 g or more of total glycoalkaloids.…”
Section: Glycoalkaloids and Potato Taste Qualitymentioning
confidence: 99%